Short-duration aman rice cultivation for crop intensification, diversification, and greenhouse gas mitigation (Bangla) - Ahmed, Sharif; Miajy, Abu Abdullah; Hasun, Md. Rokibul (International Rice Research Instittute, 2025)
This knowledge product introduces short-duration aman rice cultivation as an effective strategy for crop intensification, diversification, and greenhouse gas mitigation in Bangladesh. Farmers commonly growing aman rice cultivation typically requires a longer growing period, which limits the potential for additional cropping in the rabi season and results in higher methane emissions due to prolonged field presence. Short-duration aman rice varieties allow farmers to harvest in a shorter time frame, enabling multiple cropping cycles and enhancing overall productivity. This approach fosters crop diversification by freeing up land and resources for other food and cash crops, which improves farmers’ income and resilience. Additionally, the shorter growth cycles contribute to greenhouse gas mitigation by reducing methane emissions. The knowledge product aims to provide farmers, extension workers, and policymakers with practical insights into the cultivation practices, economic benefits, and environmental advantages of adopting short-duration aman rice. Scaling up this system can lead to sustainable intensification of rice production, improved food security, and climate change mitigation. Promoting this innovative approach aligns with national development goals aimed at increasing agricultural productivity, promoting diversified cropping systems, and reducing the environmental impact of rice cultivation in Bangladesh.